Determinación de hemoglobina y hematocrito en niños menores de 9 años de edad del sector Buenos Aires Sur del distrito Víctor Larco – Trujillo durante el mes de diciembre del 2010” - Reyes Zavaleta, Diana Joselyn (2011)
In the present study was to determine the hemoglobin (Hb) and hematocrit (HCT) in 51 children under 9 years old Buenos Aires Sector Southern District of Víctor Larco - Trujillo in December 2010. The blood sample was obtained fasting, using a survey to collect information about personal data, vital signs, nutritional, socioeconomic, lifestyle and health. The determination of hemoglobin was the method cyanmethaemoglobin, bringing the sample to the spectrophotometer reading at 540 nm and for hematocrit the microhematocrit method. The results expressed by sex, showing that 45.24% and 54.76% of the girls and boys respectively are within the normal values of hemoglobin, the 55.56% and 44.44% of both sexes decreased values could be due to nutritional anemia type. We analyzed the hemoglobin values according to age, found that 73.81% of children aged 4-6 years with normal hemoglobin values. With respect to hematocrit values, were normal in 43.59% and 56.41% of children respectively of the total samples and decreased values of 58.33% and 41.67% of girls and boys, being due possibly to variability nutritional and place of origin of children. Also, according to age, a higher percentage was found with normal hematocrit 87.18% between the ages of 4-6 years